2020
DOI: 10.1088/1758-5090/ab94d0
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting using hollow multifunctional fiber impedimetric sensors

Abstract: 3D bioprinting is an emerging biofabrication process for the production of adherent cell-based products, including engineered tissues and foods. While process innovations are rapidly occurring in the area of process monitoring, which can improve fundamental understanding of process-structure-property relations as well as product quality by closed-loop control techniques, in-line sensing of the bioink composition remains a challenge. Here, we report that hollow multifunctional fibers enable in-line impedimetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This latter metal-core polymer filament was produced by conventional microextrusion under pressure alike typical top-down bioprinting meaning that it is limited to room temperature materials and performances unlike the thermally-drawn fibers reviewed in this publication. Thermally drawn fibers used specifically in bioprinting include impedimetric fiber electrodes to monitor the bioprinted material in terms of cell type, differentiation stage, and survival at the nozzle during the micorextrusion process only [103]. This works shows the multi-faceted uses of fibers as they can be useful at different stages of the bioprinting process.…”
Section: Integration Of Smart Fibers In Bioprintingmentioning
confidence: 95%
“…This latter metal-core polymer filament was produced by conventional microextrusion under pressure alike typical top-down bioprinting meaning that it is limited to room temperature materials and performances unlike the thermally-drawn fibers reviewed in this publication. Thermally drawn fibers used specifically in bioprinting include impedimetric fiber electrodes to monitor the bioprinted material in terms of cell type, differentiation stage, and survival at the nozzle during the micorextrusion process only [103]. This works shows the multi-faceted uses of fibers as they can be useful at different stages of the bioprinting process.…”
Section: Integration Of Smart Fibers In Bioprintingmentioning
confidence: 95%
“…Two conductive polymer electrodes (conductive polyethylene, CPE) were incorporated into a macroscopic preform via a machining process while the center of the preform remained hollow (Figure a). We then inserted the silica fiber with a polyimide coating into the center orifice, which was then pulled down to converge with the surrounding polymer during the thermal drawing process shown in Figure b. , The optical property of the silica fiber was not altered during the fiber drawing process based on the transmission spectrum measurement before and after drawing (Figure S1). The drawn fibers were cut, bundled, and inserted into an alumina tube and fixed using phenyl salicylate (Figure c­(i)).…”
Section: Resultsmentioning
confidence: 99%
“…Custom designed 3D printed microfluidic chip was applied for spatial interaction between organoid and vasculature with a matched co-culture system. Studies have shown that during the co-culture of hESCs and chondrocytes (Chds), morphogenetic factors secreted by chondrocytes can induce hESCs to differentiate into the chondrocyte lineage ( Haring et al, 2020 ).…”
Section: Bioprinting Cell Selectionmentioning
confidence: 99%